Alcohol Promotes Exosome Biogenesis and Release via Modulating Rabs and miR-192 Expression in Human Hepatocytes - Bala, Shashi; Babuta, Mrigya; Catalano, Donna; Saiju, Aman; Szabo, Gyongyi (Frontiers in Cell and Developmental Biology, 2022)
Exosomes are membrane vesicles released by various cell types into the extracellular space under different conditions including alcohol exposure. Exosomes are involved in intercellular communication and as mediators of various diseases. Alcohol use causes oxidative stress that promotes exosome secretion. Here, we elucidated the effects of alcohol on exosome biogenesis and secretion using human hepatocytes. We found that alcohol treatment induces the expression of genes involved in various steps of exosome formation. Expression of Rab proteins such as Rab1a, Rab5c, Rab6, Rab10, Rab11, Rab27a and Rab35, which were increased at the mRNA level in primary human hepatocytes after alcohol treatment. Rab5, Rab6 and Rab11 showed significant induction in the livers of patients with alcohol-associated liver disease. Further, alcohol treatment also led to the induction of syntenin, vesicle associated membrane proteins (VAMPs), and syntaxin that all play various roles in exosome biogenesis and secretion. VAMP3, VAMP5, VAPb, and syntaxin16 mRNA transcripts were increased in alcohol treated cells and in the livers of alcohol-associated liver disease (ALD) patients. Induction in these genes was associated with increases in exosome secretion in alcohol treated hepatocytes. We found that hepatocyte enriched miR-192 and miR-122 levels were significantly decreased in alcohol treated hepatocytes whereas their levels were increased in the cell-free supernatant. The primary transcripts of miR-192 and miR-122 were reduced in alcohol treated hepatocytes, suggesting alcohol partially affects these miRNAs at the transcriptional level. We found that miR-192 has putative binding sites for genes involved in exosome secretion. Inhibition of miR-192 in human hepatoma cells caused a significant increase in Rab27a, Rab35, syntaxin7 and syntaxin16 and a concurrent increase in exosome secretion, suggesting miR-192 regulates exosomes release in hepatocytes. Collectively, our results reveal that alcohol modulates Rabs, VAMPs and syntaxins directly and partly via miR-192 to induce exosome machinery and release.